The Late Paleozoic Tectonometamorphic Evolution of Patagonia Revisited: Insights From the Pressure-Temperature-Deformation-Time (P-T-D-t) Path of the Gondwanide Basement of the North Patagonian Cordillera (Argentina) - Oriolo, Sebastián (2019)
Combined field structural analysis with in situ electron probe microanalysis Th-U-Pb monazite dating, petrologic, and microstructural data provides a reconstruction of the pressure-temperature-deformation-time (P-T-D-t) path of the Gondwanide basement of the North Patagonian Cordillera. For samples from the Challhuaco hill, the timing of development of the metamorphic S2 foliation and associated L2 lineation and tight to isoclinal F2 folds is constrained by monazite ages of 299 ± 8 and 302 ± 16 Ma during peak metamorphic conditions of ~ 650 °C and 11 kbar, achieved during prograde metamorphism and progressive deformation. Metamorphism and deformation of metamorphic complexes of the North Patagonian Andes seem to record Late Paleozoic crustal thickening and are coeval with metamorphism of accretionary complexes exposed further west in Chile, suggesting a coupled Late Devonian-Carboniferous evolution. Instead of the result of continental collision, the Gondwanide orogeny might thus be essentially linked to transpression due to advancing subduction along the proto-Pacific margin of Gondwana. On the other hand, second generation of monazite ages of 171 ± 9 and 170 ± 7 Ma constrains the timing of low-grade metamorphism related to kink band and F3 open fold development during Jurassic transtension and emplacement of granitoids. Finally, a Cretaceous overprint, likely resulting from hydrothermal processes, is recorded by monazite ages of 110 ± 10 and 80 ± 20 Ma, which might be coeval with deformation along low-grade shear zones during the onset of Andean transpression.